The future of cryptocurrency legality in Indonesia - Irma, Dasih; Maemunah, Sari; Zuhri, Saefudin; Juhandi, Nendi (Journal of Economics and Business Letters, 2021)
Cryptocurrency is a form of payment for goods and services that can be made online. Many companies have issued their own currency, often called tokens, and traded specifically for the goods or services their company provides. Currently, blockchain technology can be implemented in various elements, including, financial services, smart property, IoT, smart contracts, blockchain government, blockchain identity. In Indonesia, cryptocurrencies are interpreted as crypto assets that can only be traded on futures exchanges. There are 229 cryptocurrencies recognized in Indonesia. The legality of using Cryptocurrencies in Indonesia can only be traded on futures exchanges, as stated in the regulation of the Commodity Futures Trading Supervisory Agency (BAPPEBTI) number 5 of 2019 and the Commodity Futures Trading Supervisory Agency Regulation Number 7 concerning the Establishment of a List of Crypto Assets that can be Traded in the Physical Crypto Asset Market.